2021
DOI: 10.1155/2021/4688846
|View full text |Cite|
|
Sign up to set email alerts
|

Design of Project Cost Risk Management System Based on Improved Fuzzy Rule Weight Algorithm

Abstract: Aiming at the low accuracy of index weight calculation and risk type identification in traditional cost risk management systems, this paper proposes a project cost risk management system based on an improved fuzzy rule weight algorithm. We analyzed the types of project cost risks, adopted a three-tier technical architecture to design the system frame structure and functional organization structure of the cost risk management system, and adopted the B/S architecture for network structure deployment. In the soft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The process of formation of various expenditures cannot be accurately analyzed and predicted, and there is no set of perfect analysis methods. Huang [25] showed that the staff at the construction site and the people involved at different levels have an important influence on the project cost control of engineering projects in the power field. Xiao [26] proposed that in power engineering projects, a reasonable project cost management system can provide a decision-making basis for the control of project quality.…”
Section: Technology Cost 17mentioning
confidence: 99%
“…The process of formation of various expenditures cannot be accurately analyzed and predicted, and there is no set of perfect analysis methods. Huang [25] showed that the staff at the construction site and the people involved at different levels have an important influence on the project cost control of engineering projects in the power field. Xiao [26] proposed that in power engineering projects, a reasonable project cost management system can provide a decision-making basis for the control of project quality.…”
Section: Technology Cost 17mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi, as publisher, following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of systematic manipulation of the publication and peer-review process.…”
mentioning
confidence: 99%